Histomorphometric analysis of the response of rat skeletal muscle to swimming, immobilization and rehabilitation - Nascimento,C.C.F. (2008)
The objective of the present study was to determine to what extent, if any, swimming training applied before immobilization in a cast interferes with the rehabilitation process in rat muscles. Female Wistar rats, mean weight 260.52 ± 16.26 g, were divided into 4 groups of 6 rats each: control, 6 weeks under baseline conditions; trained, swimming training for 6 weeks; trained-immobilized, swimming training for 6 weeks and then immobilized for 1 week; trained-immobilized-rehabilitated, swimming training for 6 weeks, immobilized for 1 week and then remobilized with swimming for 2 weeks. The animals were then sacrificed and the soleus and tibialis anterior muscles were dissected, frozen in liquid nitrogen and processed histochemically (H&E and mATPase). Data were analyzed statistically by the mixed effects linear model (P < 0.05). Cytoarchitectural changes such as degenerative characteristics in the immobilized group and regenerative characteristics such as centralized nucleus, fiber size variation and cell fragmentation in the groups submitted to swimming were more significant in the soleus muscle. The diameters of the lesser soleus type 1 and type 2A fibers were significantly reduced in the trained-immobilized group compared to the trained group (P < 0.001). In the tibialis anterior, there was an increase in the number of type 2B fibers and a reduction in type 2A fibers when trained-immobilized rats were compared to trained rats (P < 0.001). In trained-immobilized-rehabilitated rats, there was a reduction in type 2B fibers and an increase in type 2A fibers compared to trained-immobilized rats (P < 0.009). We concluded that swimming training did not minimize the deleterious effects of immobilization on the muscles studied and that remobilization did not favor tissue re-adaptation.